Democracy in Central Asia: Authoritarian Regimes or Hybrid Regimes? - Tugsbilguun, T (Mongolian Journal of International Affairs, 2013)
DOI: http://dx.doi.org/10.5564/mjia.v0i18.75 Mongolian Journal of International Affairs No.18 2013: 123-126